Inside Cover: Low Band Gap Donor–Acceptor Conjugated Systems Based on 3‐Alkoxy or 3‐Pyrrolidino‐4‐cyanothiophene and Benzothiadiazole Units (Chem. Asian J. 15/2017). Issue 15 (24th July 2017) - Savitha, Gurunathan; Moussallem, Chady; Allain, Magali; Gohier, Frédéric; Frère, Pierre
Abstract : Electrodeposited conjugated polymers with donor—acceptor structures combining 3‐hexyloxy or 3‐pyrrolidino‐4‐cyanothiophene, 3, 4‐ethylenedioxythiophene (EDOT), and benzothiadiazole building blocks present electrochromic properties upon oxidation. In the presence of the pyrrolidinocyano thiophene moieties, the oxidation leads to a blue to brown color change, while with EDOT and hexyloxycyano thiophene units a switch from green to pale blue is observed. The tree of glass "The blue cedar" is an original Geneviève Péan creation (www.revedeverre.net). More information can be found in the Full Paper by Pierre Frère et al. onpage 1935 in Issue 15, 2017 (DOI:10.1002/asia.201700545 ).